An Analysis on EFL Students' Motivation in Speaking English - Soraya Fayyaza Haffez Abdullah; Nyssa Khairina; Devina Zulfa Rahmadani (Program Studi Magister Tadris Bahasa Inggris UIN Sultan Maulana Hasanuddin Banten, 2025)
This study was conducted to analyze the factors that influence students' motivation to speak English in the English Education Department at Universitas Tidar. This qualitative research involved 20 fourth-semester students, using a questionnaire to collect data on motivation levels. The results of the analysis showed that students' personal desire to improve their language skills, along with encouragement from lecturers, significantly impacted on their speaking ability. Most students showed a strong interest in improving their English and took the initiative to complete speaking tasks. However, many students also faced challenges such as low self-confidence and difficulties with new vocabulary. This research underlines the importance of creating a supportive learning environment and implementing effective teaching strategies to improve students' competence and confidence. The conclusion suggests that lecturers play an important role in motivating students, and a combination of personal encouragement and external support can result in better speaking proficiency.